Analysis of High School Students' Physics Literacy Ability Towards the Phenomenon of Elasticity Based on the Natural of Science Literacy Test Instrument - Retno Wandhira; Titin Sunarti; Oka Saputra; Binar Kurnia Prahani; Muhammad Satriawan; Hanandita Veda Saphira (Universitas Pendidikan Mandalika, 2025)
The advancement of science and technology requires students to possess strong scientific literacy, particularly in understanding physical phenomena such as elasticity. However, students often demonstrate a low conceptual understanding of elasticity in real-life contexts, posing a challenge in physics education. This study aims to analyze students’ physics literacy skills using the Nature of Science Literacy Test (NOSLiT) instrument. This research employed a descriptive quantitative approach with a sample of 30 students from classes A, B, and C. Data were collected through a written test based on the NOSLiT framework, which consists of six scientific literacy indicators, and analyzed quantitatively using achievement categories. The findings revealed that students' overall scientific literacy achievement was categorized as low (43.2%). The highest achievement was on the scientific evidence rule indicator (58.8%, moderate category), while the lowest was on science process skills (24.3%, very low category). These results suggest the need for more interactive and experiment-based instructional strategies to enhance students’ conceptual understanding. Students' responses were mostly descriptive and lacked evidence-based reasoning, with misconceptions about relationships among physics variables still apparent. These findings emphasize the importance of incorporating scientific practices—such as experimentation, evidence utilization, and contextual problem-solving—into teaching. This study was limited to a single school and instrument, which restricts the generalizability of the results. Future research should include a broader sample and adopt a mixed-method approach to obtain more comprehensive insights. Moreover, the development of inquiry-based learning models is crucial to support the advancement of students' scientific literacy.